Pengaruh Kualitas Layanan Terhadap Kepuasan Pelanggan Cv Tans Collection Di Surakarta - HARTANTI, SRI (2016)
Sri Hartanty. NPM. P100 130 007. Effect of Service Quality Customer Satisfaction CV Tans Collection at Surakarta. Thesis. Post Graduate Program of Magister Management, University of Muhammadiyah Surakarta. 2015. The objectives of this research are responsivs contribution (responsivs), assurance (assurance), physical evidence (tangible), empathy (empathy), reliability (reliability) to customer satisfaction. And contributions responsivs (responsivs), assurance (assurance), physical evidence (tangible), empathy (empathy), reliability (reliability) jointly towards customer satisfaction. The population of this research is all agencies that become customers CV Tans and taken a sample of 100 institutions. Data were collected by questionnaires that have been made previously by researchers with questions about responsivs (responsivs), assurance (assurance), physical evidence (tangible), empathy (empathy), reliability (reliability) to customer satisfaction and source of data is the consumers who use the services CV service Tans. .The result of the study in this research is the t value for the responsivs variable. t value for responsivs is 2,649. The t value of 2,649 > 0,350. It means that responsivs have contributed to customers. The t value for the assurance variable. t value for assurance is 2,664. The t value of 2,664 > 0,309. It means that assurance have contributed to customers. The t value for the tangible variable. t value for tangible is 2,125. The t value of 2,125 > 2,55 It means that tangible have contributed to customers. The t value for the emphaty variable. t value for emphaty is 2,423. The t value of 2,423 > 0,233. It means that emphaty have contributed to customers. The t value for the reliability variable. t value for reliability is 2,049. The t value of 2,049 > 0,234. It means that reliability have contributed to customers. Contributions responsivs (responsivs), assurance (assurance), physical evidence (tangible), empathy (empathy), reliability (reliability) jointly towards customer satisfaction. The value F count > 0,05 , then the model is good enough selection of variables responsivs, assurance, tangibles, empathy, and reliability are correct . Key words : Quality, Satisfaction, Customer